The state of carotid artery wall in hypertensive patients with gout based on the study of inflammatory markers - Kuzmina, H. P.; Lazarenko, O. M. (Zaporozhye Medical Journal, 2021)
The aim. To analyze the frequency of atherosclerotic lesions of the carotid arteries and association with the lipid metabolism and inflammatory markers in hypertensive patients with gout. Materials and methods. 122 patients with hypertension aged 30 to 65 years were examined (mean age (56.0 (47.0; 62.0)), including 104 men (85.2 %) and 18 women (14.8 %). Group 1 included 72 hypertensive patients with gout; group 2 – 50 hypertensive patients without gout; group 3 – 20 gout patients without hypertension. Serum levels of high sensitivity C-reactive protein were detected by enzyme-linked immunosorbent assay. Serum ferritin levels were measured using electrochemiluminescent detection. The patients underwent carotid artery ultrasound according to standard methods. Results. The duration of gout exacerbation and the pain intensity evaluated with the visual analog scale (VAS) (P < 0.01) were significantly higher in group 1, than those in group 3 (P < 0.01). Serum ferritin levels were 2.6 (P < 0.01) times higher in group 1 than those in group 2. In patients with gout, the levels of ferritin were significantly 2.1 times higher, than in group 2 (P < 0.01). The levels of hsСRP in patients of group 1 were 3.1 times higher than those in group 2 (P < 0.01). The proportion of patients with intima-media complex (IMC) thickness ≥0.9 mm was higher in group 1 than in groups 2 (χ2 = 4.58, P < 0.05) and 3 (χ2 = 24.96, P < 0.01). In the structure of plaques, isoechoic were significantly more often seen among group 1 patients as compared to group 3 (χ2 = 6.56, P < 0.01), and hyperechoic – as compared to group 2 (χ2 = 4.63, P < 0.05). Hypoechoic plaques were detected in groups 1 and 2 with similar frequency (P > 0.05). This type of plaque was associated with a high risk of cerebrovascular events. In the patients with arterial hypertension and gout, a significant moderate positive correlation was found between the IMC thickness and the serum uric acid level (rs = 0.46, P < 0.01), hsCRP (rs = 0.33, P < 0.01), age (rs = 0.33; P < 0.01), duration of gout (rs = 0.27, P < 0.05) and VAS (rs = 0.39, P < 0.01); the level of hsCRP was correlated with the presence of atherosclerotic plaques (τ = +0.64, P < 0.05). Conclusions. The combination of hypertension with gout in patients was associated with a high incidence of IMC thickness ≥0.9 mm and atherosclerotic plaques, more severe disorders of purine and lipid metabolism, increased inflammatory markers (ferritin and hsCRP), that should be considered not only in the aspect of chronic inflammation, but also as a part of the disease.